1985
DOI: 10.3168/jds.s0022-0302(85)80885-7
|View full text |Cite
|
Sign up to set email alerts
|

Successive Overrelaxation, Block Iteration, and Method of Conjugate Gradients for Solving Equations for Multiple Trait Evaluation of Sires

Abstract: A potential difficulty with mixed model equations for multiple trait evaluation of sires is solving the equations as the number of equations increases proportionally to the number of traits. Time required to obtain inverse solutions increases by the number cubed. Thus, iterative procedures often are used. Three iterative procedures, successive overrelaxation, block iteration with relaxation, and the method of conjugate gradients, were compared for four sets of multiple trait equations for sire evaluation. Equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…QUAAS et al (1984) used the square root of criterion 3 and suggested that 10 −4 would be sufficient. VAN VLECK and DWYER (1985) stated that for the purpose of ranking animals, a less precise stopping point may be required than when genetic evaluations are used to predict genetic trend. Also, all previous discussions of CC has focused on genetic evaluations of real data where computing time is often not an important factor.…”
Section: Us Copyright Clearance Center Code Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…QUAAS et al (1984) used the square root of criterion 3 and suggested that 10 −4 would be sufficient. VAN VLECK and DWYER (1985) stated that for the purpose of ranking animals, a less precise stopping point may be required than when genetic evaluations are used to predict genetic trend. Also, all previous discussions of CC has focused on genetic evaluations of real data where computing time is often not an important factor.…”
Section: Us Copyright Clearance Center Code Statementmentioning
confidence: 99%
“…Meaningful comparisons of two CC for different traits can only be arrived at by experience. VAN VLECK and DWYER (1985) stated that for the purpose of ranking animals, a less precise stopping point may be required than when genetic evaluations are used to predict genetic trend. QUAAS et al (1984) used the square root of criterion 3 and suggested that 10 −4 would be sufficient.…”
mentioning
confidence: 99%
“…Several original computing techniques have been studied to make MT‐AM feasible even on very large data sets. For example, people have extended to the multiple trait context procedures such as those referred to as “iteration on data” which decreases core memory requirements (S chaeffer and K ennedy 1986), “Reduced Animal Model” which decreases the size of the linear system to solve (Q uaas and P ollak 1981), or more sophisticated iterative methods such as the method of conjugate gradients (V an V leck and D wyer 1985).…”
Section: Introductionmentioning
confidence: 99%